(untitled) (Global Journal of Science Frontier Research, 2012)
The intent of this paper is to establish a common fixed point theorem for two pairs of occasionally weakly compatible single and set-valued maps satisfying a strict contractive condition in a non -Archimedean fuzzy metric space.